Tribological behavior and biocompatibility of novel Nickel-Free stainless steel manufactured via laser powder bed fusion for biomedical applications - Nayak, Chinmayee (Elsevier, 2025)
Due to the risk of releasing carcinogenic nickel ions from conventional 316L stainless steel under a corrosive human body environment, a new variant of steel termed nickel-free stainless steel (NiFSS) has been investigated. The present study investigates the tribological properties and biocompatibility of NiFSS manufactured via laser powder bed fusion (PBF-LB/M). The ferritic NiFSS exhibited significantly lower coefficient of friction (0.08 to 0.28) and wear rate (1.60 × 10-6 mm3/Nm to 6.60 × 10-6 mm3/Nm) compared to reported values for austenitic 316L SS, under both dry and simulated body fluid (SBF) conditions and various sliding geometries. This improvement is attributed to the superior hardness (3.394 ± 0.1340 GPa) and elastic modulus (238 ± 9.0797 GPa) of NiFSS. To assess the biocompatibility, the viability of mouse pre-osteoblastic MC3T3-E1 cells was evaluated with an Alamar Blue assay when the cells were cultured on top of PBF-LB/M built NiFSS and 316L SS samples. The results indicated that even though cell growth was most optimal on regular cell culture plastic, cell viability was better maintained on PBF-LB/M built NiFSS compared to 316L SS. Therefore, the results of the present study propose that PBF-LB/M fabricated NiFSS holds promise for application in biomedical devices for joint arthroplasty.